Comparison of 16S rDNA Next Sequencing of Microbiome Communities From Post-scalder and Post-picker Stages in Three Different Commercial Poultry Plants Processing Three Classes of Broilers - Wages, Jennifer A.; Feye, Kristina M.; Park, Si Hong; Kim, Sun Ae; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Poultry processing systems are a complex network of equipment and automation systems that requires a proactive approach to monitoring in order to protect the food supply. Process oversight requires the use of multi-hurdle intervention systems to ensure that any undesirable microorganisms are reduced or eliminated by the time the carcasses are processed into final products. In the present study, whole bird carcass rinses (WBCR) collected at the post-scalder and post-picker locations from three different poultry processing facilities (Plant A: mid-size broiler processing, B: large size broiler processing, C: whole Cornish broiler processing) were subjected to next generation sequencing (NGS) and microbial quantification using direct plating methods to assess the microbial populations present during these stages of the poultry process. While direct plating methods quantified some of the microorganisms present, and demonstrated that reductions in aerobic plate count (APC) and Enterobacteriaceae (EB) were not consistent between the two sampling locations for all facilities, the application of NGS provided a more complete characterization of the microbial communities present on processed broiler carcasses. While the foodborne pathogens typically associated with raw poultry, Salmonella and Campylobacter, were not identified, sequence analysis performed by Quantitative Insights of Microbiology Ecology (QIIME) indicated shifts of Erwinia, Serratia and Arcobacter, which are microorganisms closely related to Salmonella and Campylobacter. Additionally, the presence of Chryseobacterium and Pseudomonas at both sampling locations and at all three facilities provides evidence that these microorganisms could potentially be utilized to assess the performance of multi-hurdle intervention systems.